2004
DOI: 10.1248/cpb.52.1005
|View full text |Cite
|
Sign up to set email alerts
|

Six Immunosuppressive Features from an Ascomycete, Zopfiella ion gicaudata, Found in a Screening Study Monitored by Immunomodulatory Activity

Abstract: In a screening study on immunomodulatory fungal metabolites, three known anthraquinones, carviolin (roseo-purpurin) (1), 1-O-methylemodin (2), w w-hydroxyemodin (citreorosein) (4), and a new anthraquinone, w w- together with a known steroid, ergosta-4,6,8(14),22-tetraen-3-one (5) and a new steroid, 25-hydroxyergosta-4,6,8(14),22-tetraen-3-one (6) were isolated from an Ascomycete, Zopfiella longicaudata, and found to have moderate immunosuppressive activities. The structure-activity relationships of these metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 23 publications
(22 reference statements)
3
41
0
2
Order By: Relevance
“…1). Then, in 2000 we reported the isolation and planar structures of TT-1 (1a) and 2 (2), two new immunosuppressive constituents from T. terrophilus. 6) Almost at the same time, Hayakawa et al reported the isolation of rasfonin, a new apoptosis inducer from an Ascomycete, Talaromyces sp.…”
mentioning
confidence: 99%
“…1). Then, in 2000 we reported the isolation and planar structures of TT-1 (1a) and 2 (2), two new immunosuppressive constituents from T. terrophilus. 6) Almost at the same time, Hayakawa et al reported the isolation of rasfonin, a new apoptosis inducer from an Ascomycete, Talaromyces sp.…”
mentioning
confidence: 99%
“…12,13 Esta é a primeira ocorrência desses esteroides em espécies de Penicillium. Os dados de RMN ¹H e ¹³C de 5 e 6 estão dispostos da Tabela 1.…”
Section: Resultsunclassified
“…As substâncias 1, 2 e 3 foram identificadas por análise dos espectros de RMN 1D e 2D, EM e por comparação com a literatura e mostraram total similaridade para os policetídeos citreoroseina (1), emodina (2) e janthinona (3) [8][9][10].…”
Section: Identificação Dos Policetídeosunclassified